Sensing Athletes: Sensory Dimensions of Recreational Endurance Sports - Stefan Groth; Yonca Krahn (Journal of Ethnology and Folkloristics)
Sport has become increasingly popular with recreational athletes over the last couple of decades. This has only gained minimal attention so far from scholars interested in the relations between recreational sports and everyday culture. With this paper, we seek to contribute to this field by scrutinising the sensory dimensions of recreational sport. Rather than probing into or highlighting isolated senses, we look at sensory dimensions understood as a combination of different, non-separable sensory experiences featured in recreational endurance sports. We are interested in how senses play a role for recreational endurance athletes in running, triathlon and cycling both in training and competition. We start by examining how cultural and social dimensions are inextricably linked to doing sports. Secondly, we show how different configurations of the senses and their communicative mediation are contingent on sport disciplines, specific settings, technology, development and change as sensory careers over time. Thirdly, we discuss the kinaesthetic dimensions of doing sports in relation to the senses and the role of atmospheres. We conclude by arguing that highlighting specific senses by athletes is a cultural practice that calls for a holistic analysis of senses in sport, and outline some methodological implications for research on the senses.